Mutant Taq DNA polymerases with improved elongation ability as a useful reagent for genetic engineering - Yamagami, Takeshi; Ishino, Sonoko; Kawarabayasi, Yutaka; Ishino, Yoshizumi (Frontiers in Microbiology, 2014)
DNA polymerases are widely used for DNA manipulation in vitro, including DNA cloning, sequencing, DNA labeling, mutagenesis, and other experiments. Thermostable DNA polymerases are especially useful and became quite valuable after the development of PCR technology. A DNA polymerase from Thermus aquaticus (Taq polymerase) is the most famous DNA polymerase as a PCR enzyme, and has been widely used all over the world. In this study, the gene fragments of the family A DNA polymerases were amplified by PCR from the DNAs from microorganisms within environmental soil samples, using a primer set for the two conserved regions. The corresponding region of the pol gene for Taq polymerase was substituted with the amplified gene fragments, and various chimeric DNA polymerases were prepared. Based on the properties of these chimeric enzymes and their sequences, two residues, E742 and A743, in Taq polymerase were found to be critical for its elongation ability. Taq polymerases with mutations at 742 and 743 actually showed higher DNA affinity and faster primer extension ability. These factors also affected the PCR performance of the DNA polymerase, and improved PCR results were observed with the mutant Taq polymerase.